(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper proposes a high capacity reversible image watermarking scheme based on integer wavelet transforms. The proposed scheme divides an input image into non-overlapping blocks and embeds a watermark into the high frequency wavelet coefficients of each block. The conditions to avoid both underflow and overflow in the spatial domain are derived for an arbitrary wavelet and block size. The payload to be embedded includes not only messages but also side information used to reconstruct the exact original image. To minimize the mean-squared distortion between the original and the watermarked images given a payload, the watermark is adaptively embedded into the image. The experimental results show that the proposed scheme achieves higher embedding capacity while maintaining distortion at a lower level than the existing reversible watermarking schemes.